FINANCIAL LITERACY ASSISTANCE FOR VILLAGE BUSINESS: CASE STUDY IN SITIO TAMALE, THE PHILIPPINES - Limboonngam, Nutnicha; Fernando, Kenny (Universitas Pelita Harapan, 2022)
A business really needs adequate records to evaluate business operational activities and determine future improvement steps. 30 Youths in Sitio Tamale Village, Philippines have developed a Mushroom Business which took place since October 2021. The Research Team was entrusted with two modules consisting of series A and B and aiding answer the need for mushroom Business development in the village. Module A on financial literacy knowledge and Module B on the technical steps of making financial reports are solutions to these needs. By presenting material that is practical knowledge and active interaction through filling out modules related to financial literacy, the training team explained via Google Meets to participants. The results of the assistance showed that 33% of participants understood very well, 37% of participants understood and 30% were neutral. There are several obstacles such as internet access, data processing technology capabilities, educational background, and commitment to be the main factors in this training. There are several key issues including challenges, risks, and further opportunities for village business. This financial literacy assistance could be an incubator to effectively oversee the business health.